(99m)Tc-MIBI emboli in the lungs detected on SPECT/CT: a pitfall in parathyroid scan - (:unkn) unknown (My University, 2014)
Although we are familiar with artifactual, focal pulmonary F-FDG accumulations without an apparent underlying pathologic finding, similar artifact for Tc-MIBI has not been described yet. Herein, we reported incidental detection of Tc-MIBI emboli in the lungs on parathyroid SPECT/CT.
Keywords: Female; Humans; Middle Aged; Tomography, X-Ray Computed; Lung; Embolism; Incidental Findings; Tomography, Emission-Computed, Single-Photon; Technetium Tc 99m Sestamibi; Multimodal Imaging; Parathyroid Glands